Persistence of epiphytic lichens along a tephra-depth gradient produced by the 2011 Puyehue-Cordón Caulle eruption in Parque Nacional Puyehue, Chile - Nelson, Peter R; Wheeler, Tim B (Bosque (Valdivia), 2017)
Lichens, symbioses between fungi and algae or cyanobacteria, are diverse and abundant in humid temperate forests in mountain ranges such as the Andes. They are also sensitive to changes in atmospheric conditions. We suspected lichens would show die back as a result of tephra fall from the 2011 Puyehue-Cordon Caulle volcanic eruption. We measured macrolichen community composition six months after initiation of the Caulle eruption at four sites along a tephra depth gradient from 10 to 50 cm. We also monitored the lichen community on permanent tree-bole quadrats over the next three years. We found 81 macrolichens species on seven plots at four sites across the tephra depth gradient. Plot species richness ranged between 23 and 34 lichen taxa. Nearly three years after the eruption, lichens in quadrats on tree boles showed no obvious trend of mortality in response to depth of tephra deposition. We concluded that lichen communities, despite being sensitive to atmospheric conditions, were able to survive the disturbance of up to 50 cm of tephra deposition three years after the eruption in part because of their position on the vertical sides of tree boles, which prevented abrasive impact and smothering by tephra deposition.